2020
DOI: 10.1093/nar/gkaa1048
|View full text |Cite
|
Sign up to set email alerts
|

Targeting OGG1 arrests cancer cell proliferation by inducing replication stress

Abstract: Altered oncogene expression in cancer cells causes loss of redox homeostasis resulting in oxidative DNA damage, e.g. 8-oxoguanine (8-oxoG), repaired by base excision repair (BER). PARP1 coordinates BER and relies on the upstream 8-oxoguanine-DNA glycosylase (OGG1) to recognise and excise 8-oxoG. Here we hypothesize that OGG1 may represent an attractive target to exploit reactive oxygen species (ROS) elevation in cancer. Although OGG1 depletion is well tolerated in non-transformed cells, we report here that OGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…TH5487 is a selective OGG1 inhibitor that binds OGG1’s active site, causing accumulation of genomic 8-oxoG lesions as detected by mass spectrometry [ 13 ]. Consistently, immunostaining of 8-oxoG lesions and a modified comet assay have both demonstrated that TH5487 treatment indeed results in an increase in 8-oxoG level in DNA [ 42 , 43 ]. We show that TH5487 does not engage with recombinant NEIL1 ( Figure 1 ) excluding an off-target interaction between TH5487 and NEIL1.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…TH5487 is a selective OGG1 inhibitor that binds OGG1’s active site, causing accumulation of genomic 8-oxoG lesions as detected by mass spectrometry [ 13 ]. Consistently, immunostaining of 8-oxoG lesions and a modified comet assay have both demonstrated that TH5487 treatment indeed results in an increase in 8-oxoG level in DNA [ 42 , 43 ]. We show that TH5487 does not engage with recombinant NEIL1 ( Figure 1 ) excluding an off-target interaction between TH5487 and NEIL1.…”
Section: Discussionmentioning
confidence: 82%
“…Inhibition of OGG1 by TH5487 results in accumulation of genomic 8-oxoG lesions [ 13 , 42 , 43 ]. Similarly, we show here that siRNA-mediated OGG1 depletion also leads to accumulation of 8-oxoG lesions in DNA after menadione treatment ( Figure 6 b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in case of deficient or overwhelmed repair in response to an important level of oxidative damage, the level of replicative stress and subsequent DSB are increased leading to cell death. Thus, it has been recently proposed than BER proteins, such as OGG1, could be potential targets for cancer treatment [71].…”
Section: Oxidative Lesions: "Natural" Causes Of Replicative Stressmentioning
confidence: 99%